Multiuser MIMO systems, worst case noise and transmitter cooperation - Bosche, H.; Jorswieck, E.A. (ISSPIT 2003 : proceedings of the 3rd International Symposium on Signal Processing and Information Technology : 14-17 December, 2003, Maritim Rhein/Main Hotel, Darmstadt, Germany, 2003)
The capacity of a cellular MIMO system is limited by the additive white Gaussian noise, intracell interference from the other users within the cell and by intercell interference from users outside the considered cell. The receiver as well as the transmitter have perfect channel state information. We are interested in the limits of the MIMO channel capacity under the different types of noise plus interference. Therefore, we consider three scenarios in which the noise is subject to different constraints. In all scenarios the achievable capacity of the MIMO system with worst case noise is equal to the capacity of some MIMO system in which either the channels are orthogonal or the transmit antennas are not allowed to cooperate. Furthermore, the minimax expressions fulfill a saddle point property.